Jigsaw Learning Model Improves Student Learning Outcomes In Mechanical Engineering Basic Knowledge - Gede Widayana; Kevin Balsono (Universitas Pendidikan Ganesha, 2023)
There are still many students who get scores below the average. Teachers still use conventional learning models that make students less motivated to learn. This study aims to analyze the effect of the jigsaw cooperative learning model on the learning outcomes of class X students in the subject of basic knowledge of mechanical engineering. This study used a posttest-only group design. The population of this research is class X Welding Engineering students. Sampling was done by using a random sampling technique. The first sample (class A), totaling 30 students, is an experimental class. The second sample (class B), totaling 30 students, is the control class. The methods used in data collection are the documentation and test methods. Data analysis of the two groups used descriptive statistical analysis and inferential statistical analysis through independent sample t-tests. The results showed differences in the learning outcomes of students' basic knowledge of mechanical engineering in the experimental class taught using the jigsaw learning model using conventional learning models. It was concluded that the jigsaw learning model could improve student learning outcomes in mechanical engineering subjects.